Comparison between multi-objective and single-objective optimization for the modeling of dynamic systems - Mohd Zakimi, Zakaria; Hishamuddin, Jamaluddin; Robiah, Ahmad; Sayed Mohammad Reza, Loghmanian (SAGE Publications, 2013)
Link to publisher's homepage at http://pii.sagepub.com/